NUMERICAL SIMULATION OF ACID INFLUENCE ON THE BOTTOM THROOM ZONE OF OIL FIELDS WITH CARBONATE RESERVOIRS TAKEN INTO ACCOUNT OF ROC FRACTURING - Burnashev V.F; Izzatullaeva F.Sh (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The paper considers the problem of modeling the acid impact on the bottomhole zone of oil fields with carbonate fractured-porous reservoirs. The process is modeled within the framework of the mechanics of multicomponent multiphase filtration using averaged values ​​of filtration-capacitance parameters taking into account chemical kinetics. Based on the proposed mathematical model in a flat-radial setting, the advancement of acid and changes in the filtration characteristics of the bottomhole zone of the formation during the injection of the reagent are studied. The influence of acid solution injection modes on the processes occurring in the near-wellbore zone of the formation is assessed. Numerical calculations were performed and the process characteristics were determined.